Exploring transnational LGBTQI+ solidarities: A scoping review protocol on the complexities, theories, and models - Reem Alameddine; Ahmed Hamila; Edward Ou Jin Lee (PLoS ONE, 2025)
On August 28, 2022, the Government of Canada unveiled its first Federal Action Plan to promote LGBTQI+ equality, committing to significant international investments and diplomatic initiatives. While these initiatives are viewed positively by some experts, others critique them as manifestations of homonationalism or homocolonialism, perpetuating colonial legacies and neoliberal norms. These debates underscore the complexities of transnational LGBTQI+ solidarity, particularly within the Majority World, shaped by colonial histories. This scoping review protocol aims to critically assess the empirical literature on transnational LGBTQI+ solidarities, to map, compare, and contrast various configurations of LGBTQI+ transnational solidarities, while also highlighting the different theories and methodologies employed in research on these topics. We will systematically search social science databases for relevant studies, emphasizing literature from peer-reviewed journals. In the study selection process, we will include research using primary sources and systematic reviews, while excluding the grey literature and non-peer-reviewed sources. Data will be charted using the COVIDENCE software, with rigorous inclusion criteria and a detailed data extraction process. The review will synthesize findings to identify key themes, gaps in knowledge, and provide policy and practice recommendations. Our goal is to map and compare different LGBTQI+ transnational solidarity strategies, contributing to a deeper understanding of these complex issues, ultimately informing future research and policy development in the field of LGBTQI+ rights on a global scale. The results will help develop a comprehensive understanding of the issues and propose a future research agenda.